Does trade reduce infant mortality? Evidence from sub-Saharan Africa. (April 2020) - Panda, Pallavi
Highlights: African Growth and Opportunity Act reduces infant mortality by 9% of sample mean. Event study reveals that there exists no effect prior to AGOA being implemented. Evidence of strong heterogeneous effects at the country and household level. Employed women in agriculture or in manual labor see a greater benefit. Income seen as a potential channel for the dynamic treatment effects. Abstract: Trade can affect the development process of a country via various direct and indirect mechanisms. Empirically, it is difficult to identify causal effects, as trade is likely to be endogenous to other socio-economic factors that also affect development. To overcome this problem, this study uses a trade policy experiment called the African Growth and Opportunity Act (AGOA) which conferred many sub-Saharan African countries largely duty-free and quota-free access to US markets. Using retrospective birth histories from Demographic and Health Survey (DHS), I develop a large micro panel dataset that spans 30 sub-Saharan African countries and carry out a within-mother variation in survival of infant to find a causal impact of the policy. Identification in this analysis is based on each country's exposure to the trade policy at different points in time. I find that the policy reduces infant mortality by about 9% of the sample mean, even after controlling for country-time linear trends as well as mother's time invariant characteristics. Event study reveals no effects prior to AGOA implementation, corroborating that the decrease in infant mortality is due to AGOA. I also find strong heterogeneous effects at the country and household level. The effects range from there being no significant effect to a strong increase or a strong decrease in infant deaths at the country level. The effect of AGOA on infant survival is stronger for countries that export large amounts of agricultural goods and mineral ores as compared to oil exporting countries. At the micro level, I see stronger effects for the uneducated, rural, and poor women via those women employed in agriculture or using manual labor, indicating increasing incomes as a possible mechanism. This study provides the first estimates of the effects of AGOA on infant mortality and adds to the literature on the quantitative impact of trade on health.